Governance of projects in public procurement of innovation a multi-level perspective. Issue 2 (8th April 2020) - Talebi, Alireza; Rezania, Davar
Abstract : Purpose: Governance of projects is a dynamic process that involves the interaction of agents, opportunities, rules, instruments and legitimacy. The authors conducted a case study of the governance of exploratory projects in public procurement of innovation in a local government. The authors consider both contextual aspects that impose requirements on the procurement process and procedural aspects of how the different actors interact with each other. In particular, the purpose of this study is to investigate how actors make sense of the projects and how governance evolves over their lifetime. Design/methodology/approach: To engage in an open-system investigation of exploratory public procurement of innovation (PPI) projects, the authors adopted a case study approach in which they collected a variety of data including publicly available documentary evidence, interviews with project participants and project evaluation reports. The authors used transcripts of 17 interviews with project participants conducted independently to gain an initial understanding of the case. They conducted additional semi-structured interviews with projects' participants (ten interviews in total) and used theory-driven analysis (Pawson and Tilley, 1997 ) based on Borrás and Edler's (2014 ) model of governance. Findings: The authors identified four stages – problem identification, partner selection, partnership development and evaluation and commercialization – these projects. The case demonstrates how governance changes in each stage and at the three levels of policy, network and projects. Each level has its own governance pillar. The results suggest that a multi-level perspective (MLP) can be a fruitful framework to study governance of projects in these contexts. Research limitations/implications: The authors note that the number of participants in the network of this case is not very large. Other organizations that aim to adopt PPI may need to pay attention to the complementarity and the number of partners in the network. In this case, organizations were motivated to collaborate as each had its own objectives which were distinct but complementary. Practical implications: Co-creation of value is currently a topic of interest for public policy reform across the globe. The case indicates that procurement for innovation requires a degree of coordinated change across governmental departments, such as planning, legal and procurement to implement the policy and related support systems. Furthermore, the authors observed that a portfolio approach to inter-organizational collaboration with different partners was effective. Each partner has its own objective, but they complement one another. A portfolio of different, though complementary, inter-organizational arrangements enables various complementary instruments and various logics to be used. Social implications: The public sector is an important actor in driving innovation in products and services that fulfill societal needs. This is explored in public procurement of innovation. In this process, several partners from private and public sectors are involved. This partnership is mainly used to co-create the value and encourage innovation to benefit the citizens. However, to serve this goal, the case indicates that procurement for innovation requires a degree of coordinated change across governmental departments, such as planning, legal and procurement to implement the policy and related support systems. For this phenomenon MLP should be used as an inclusive framework to study socio-technical change. Originality/value: The analysis of the case presented in this study demonstrates that even in the case of temporary public procurement of innovation projects, governance is layered. The three pillars of governance not only interact at each layer but also communicate across layers. Even though the interaction of the three pillars of governance is well established in the literature on socio-technical change, the interaction across levels in the context of temporary projects is novel. The authors contribute to the literature on governance of such projects by highlighting the stratification of governance.